THE EFFECTIVENESS OF ACUPRESSURE ON THE HEGU AND SANYINJIAO POINTS FOR DYSMENORRHEA IN ADOLESCENTS - Maftuchah Maftuchah; Annisa Nurul Afifah; Mei Lia Zulis Windyarti; Rose Nur Hudhariani (Universitas Karya Husada Semarang, 2025)
Dysmenorrhoea is lower abdominal pain caused by uterine muscle contractions and is a common problem among adolescents. In 2020, Indonesia reported that 64.25% of adolescents experienced dysmenorrhoea. Effective management is essential because dysmenorrhoea can negatively affect adolescents’ daily activities and concentration during learning. One non-pharmacological technique that can be used is acupressure at the hegu (LI4) and sanyinjiao (SP6) points combined with lemon aromatherapy. This study aimed to analyse the effectiveness of acupressure at the LI4 and SP6 points combined with lemon aromatherapy in reducing primary dysmenorrhoea among adolescents. This quantitative study employed a quasi-experimental design with 36 respondents selected through purposive sampling. The intervention consisted of applying pressure to the LI4 and SP6 points for 30 minutes and administering lemon aromatherapy by diluting 3 drops of lemon essential oil in 10 ml of water, carried out once daily for two days starting from the onset of dysmenorrhoea. The results showed that acupressure at both the hegu and sanyinjiao points combined with lemon aromatherapy significantly reduced dysmenorrhoea, with no significant difference in effectiveness between the two points (p = 0.486). Schools support the use of acupressure and lemon aromatherapy as an accessible and non-pharmacological method to help adolescents manage dysmenorrhoea.